Restoring an old concept of Pholeuonopsis (=Blattodromus syn. nov.) and new recombination for one species from the Balkan Peninsula (Insecta, Coleoptera, Leiodidae, Cholevinae, Leptodirini) - Čeplík, Dávid (Zootaxa, 2021)
After morphological study and comparison with related material, the following synonymy is proposed: Pholeuonopsis Apfelbeck, 1901 (=Blattodromus Reitter, 1904 syn. nov.). A redescription of the genus Pholeuonopsis Apfelbeck, 1901 is given.